Optimasi kekuatan tarik komposit polyester diperkuat serat sisal dengan filler serbuk gergaji kayu sengon menggunakan metode respon surface - Okariawan, IDK.; Fajar, M.; Hidayatullah, S. (Dinamika Teknik Mesin, 2016)
Composite is an engineering material, which is made from combination of two or more different materials into a new material with new properties. The aim of this research is to investigate optimum composition of sisal fiber reinforced sawdust sengon filled polyester composites on the tensile strength using respon surface methodology.The testing of tensile strength is based on ASTM D 3039 standard. It has dimension 6 mm in thick, 25 mm in width and 340 mm in length. The composites are made by using compaction method. The volume fraction of sisal fiber is 25%, 30% 35%, 40% and 45%. The ratio matrik with filler is varied 5, 10, 15, 20 and 25. The fiber length is 90 mm and the direction of fiber orientation is random.The results shows that the respon surface methodology capable to search value of independent variables to give optimum values of tensile strength. The application of respon surface methodology for the research optimation composition of sisal fiber reinforced sawdust sengon filled polyester composites on the tensile strength showed that the optimum value of tensile strength response could be achieved at volume fraction of sisal fiber 38,6565% and ratio matrik with filler 24,601.